Hypoxic Non-replicating Persistent Mycobacterium tuberculosis Develops Thickened Outer Layer That Helps in Restricting Rifampicin Entry - Jakkala, Kishor; Ajitkumar, Parthasarathi (Frontiers in Microbiology, 2019)
Bacteria undergo adaptive morphological changes to survive under stress conditions. The present work documents the morphological changes in Mycobacterium tuberculosis (Mtb) cells cultured under hypoxic condition using Wayne’s in vitro hypoxia model involving non-replicating persistence stages 1 and 2 (NRP stage 1 and NRP stage 2) and reveals their physiological significance. Transmission electron microscopy of the NRP stage 2 cells showed uneven but thick outer layer (TOL), unlike the evenly thin outer layer of the actively growing mid-log phase (MLP) cells. On the contrary, the saprophytic Mycobacterium smegmatis NRP stage 2 cells lacked TOL. Scanning electron microscopy and atomic force microscopy of the Mtb NRP stage 2 cells confirmed the rough uneven surface unlike the smooth surface of the MLP cells. Zeta potential measurements showed high negative charge on the surface of NRP stage 2 cells and polysaccharide specific calcofluor white staining of the cells revealed high content of polysaccharide in the TOL. This observation was supported by the real-time PCR data showing high levels of expression of the genes involved in the synthesis of sugars, such as trehalose, mannose and others, which are implicated in polysaccharide synthesis. Experiments to understand the physiological significance of the TOL revealed restricted entry of the biologically low-active 5-carboxyfluorescein-rifampicin (5-FAM-RIF), at concentrations equivalent to microbicidal concentrations of the unconjugated biologically active rifampicin, into the NRP stage 2 cells, unlike in the MLP cells. Further, as expected, mechanical removal of the TOL by mild bead beating or release of the NRP stage 2 cells from hypoxia into normoxia in fresh growth medium also significantly increased 5-FAM-RIF permeability into the NRP stage 2 cells to an extent comparable to that into the MLP cells. Taken together, these observations revealed that Mtb cells under hypoxia develop TOL that helps in restricting rifampicin entry, thereby conferring rifampicin tolerance.